Strategi Komunikasi Fakultas Dakwah dan Ilmu Komunikasi UIN Imam Bonjol Padang dalam Meningkatkan Jumlah Mahasiswa - Feni Permata Sari; Alkendra Alkhendra; Usman Usman; Arina Fransiska (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2019)
This research was motivated by an increase in the number of students in 2013 up to 2016 at the Da'wah and Communication Faculty of the State Islamic Institute of Imam Bonjol Padang. The author wants to know how the faculty communication strategy in increasing the number of students, which includes promotional messages, promotional media and promotional effects. The research method used is qualitative descriptive. The research informants were taken from the academics involved in the faculty and student promotion activities of the class of 2013 until 2016. The technique of determining informants used the snowball technique. The technique of collecting data through observation, interviews and documentation studies. The results obtained are communication strategies used by the faculty in terms of promotional messages, namely verbal messages such as face to face dialogue, and non-verbal messages such as direct activities in the field. Judging from the promotional media used, namely direct media, including collaborative visits, seminars, and workshops. Indirect media such as brochures, posters, calendars, bags, websites, and the work of students, students and alumni. Judging from the promotional effects, the first cognitive effect, including the increase in knowledge of prospective students regarding the Faculty of Da'wah and Communication Sciences. The second is affective effects, including changes in attitudes of prospective students after knowing the information. the third is the behavioral effect, including decisions and actions taken by prospective students after receiving and understanding information about the Da'wah and Communication Sciences